Patient with Rosai-Dorfman-Destombes disease: 18F-FDG-PET/CT scan as a diagnostic tool - Araujo Cachay, Luis C. (2023)
Rosai-Dorfman-Destombes disease (RDD) is a rare non-Langerhans cell histiocytosis, with sinus involvement and massive lymphadenopathy. RDD is usually self-limited; it can appear alone or related to other diseases. We present a 9-year-old male with biopsy of that lesion was taken, giving as result a benign histiocytosis, compatible with RDD. The patient was scanned with full body 18F-FDG PET/CT, the results of the study showed hypermetabolic focal lesions in the sphenoid sinus, ethmoid sinus, and bilateral nasal involvement with hypermetabolic focal injury in the middle third of the left tibia, findings in relation to high-grade expansive injury. The study of 18F-FDG PET/CT demonstrated avid FDG lesions at nodal and extranodal sites, and it also can be used in monitoring and/or evaluating response to treatment.